The Effect of Coping on Family Health in Dealing with COVID-19 Pandemic - Sugeng Mashudi; Sri Susanti; Sulistyo Andarmoyo; Elok Yulidaningsih; Yuzana binti Mohd Yusop (Faculty of Medicine, University of Jember, 2021)
The emergence of the COVID 19 pandemic is perceived as an unprecedented pressure. If the pandemic is prolonged, it will be able to reduce family health. This study provides an analysis of the effect of coping on family health in dealing with COVID 19. Researchers use the family health theory approach to answer the research objectives. Using a sampling quota, an online survey of 90 respondents throughout Indonesia. The results showed that 15% of family health is determined by the family's coping during the face of the COVID 19 pandemic. It is necessary to apply various coping strategies to support optimal family health. Keywords: COVID 19, coping, family health, pressure.